Persepsi Aparatur PA Bandung Terhadap Efektivitas Penggunaan E-Court - Athiyah, Rosyiqah; Mujahid, Ilham; Rojak, Encep Abdul (UNISBA Press, 2025)
Abstract. The digital transformation of Indonesia's judicial system is marked by the implementation of the e-Court system as part of the effort to modernize legal bureaucracy. This study aims to analyze the effectiveness of the e-Court system in facilitating case processes at the Religious Court of Bandung from 2022 to 2024. This research employs a descriptive qualitative method with an empirical juridical approach, using observation, interviews, and document analysis. The findings reveal that the e-Court system has simplified administrative procedures such as case registration, fee payments, and party summons. However, the use of the e-Litigation feature remains limited due to digital literacy gaps, inadequate infrastructure, and reluctance from disputing parties. An analysis based on public service theory and digital bureaucracy indicates that although the system has improved efficiency and transparency, its implementation has yet to be fully inclusive. Therefore, enhancing public outreach, improving digital infrastructure, and providing training for court personnel are essential to realizing the principles of a simple, fast, and low-cost judiciary Abstrak. Penelitian ini bertujuan untuk menganalisis efektivitas penerapan sistem e-Court dalam mempermudah proses penyelesaian perkara di Pengadilan Agama Bandung. Melalui pendekatan yuridis empiris, penelitian ini menemukan bahwa meskipun e-Court telah berhasil menyederhanakan proses administrasi perkara, seperti pendaftaran dan pembayaran biaya perkara, implementasinya belum optimal terutama pada tahap e-Litigation. Faktor-faktor seperti literasi digital masyarakat yang rendah, keterbatasan infrastruktur, serta kesiapan internal aparatur pengadilan menjadi kendala utama. Temuan ini dianalisis menggunakan teori pelayanan publik dan birokrasi digital. Kesimpulannya, sistem e-Court telah membawa kemajuan signifikan, namun dibutuhkan upaya berkelanjutan untuk meningkatkan pemanfaatannya secara inklusif dan merata